Single injection thoracic paravertebral block (TPVB) for breast surgery in morbidly obese patient - Anita Kulkarni; Vedapadmapriya Selvakumar; Namrata Gupta (Asian Journal of Oncology, 2017)
Morbidly obese (MO) patients with associated restrictive airway disease, obstructive sleep apnea, and coronary artery disease pose challenge to an anesthesiologist. Regional block combined with general anesthesia (GA) is the anesthetic technique of choice as it will decrease the requirement of opioids, anesthetics, and postoperative respiratory depression. A MO patient for modified radical mastectomy was successfully managed with single-injection thoracic paravertebral block and conventional GA.